Tower Planning And Arrangements Mobile Telecommunication District Central Aceh With Methode Fuzzy Clustering - Safwani, Eva; Firdausi, Ahmad; Hakim, Galang (Universitas Muhammadiyah Yogyakarta, 2021)
Advances in technology, especially in the telecommunications industry has been progress rapidly. Various types of cellular communication systems began operating by covering targeted service areas throughout Indonesia even to the corners of the archipelago, operators continue to try to build infrastructure so that service and the quality is increasing. One of the on going infrastructure developments is Base Transceiver Station (BTS). However, BTS development infrastructure must consider the aesthetics and compliance with the Regional Spatial Plan an area to determine the potential location of tower construction optimally. In this paper we propose the Fuzzy Clustering and Harmony Search to optimize the placement of potential new tower locations. In the optimization process using several parameters such as total population, total area, and shared tower needs for the next 5 (five) years. The results of optimization show that needs BTS in 2024 network services require an additional 74 BTS and supported by 21 new towers together.